Tristetraprolin (TTP) as a Therapeutic Target in Inflammatory Disease - Patial, Sonika (Trends Pharmacol Sci, 2016)
Members of the tristetraprolin (TTP) family of RNA binding proteins are found in all major eukaryotic groups. Family members from plants through humans can bind AU-rich elements in target mRNAs with high affinity. In mammalian cells, these proteins then promote deadenylation and decay of target transcripts. Four such proteins are found in the mouse, of which the best studied is TTP. When its gene is disrupted in the mouse, the animals develop a severe syndrome of arthritis, autoimmunity, cachexia, dermatitis, and myeloid hyperplasia. Conversely, recent overexpression studies have demonstrated protection against several experimental models of immune inflammatory disease. This endogenous anti-inflammatory protein could serve as the basis for novel approaches to therapy of similar conditions in humans.